Dynamic Determinants of Longevity and Exceptional Health. (5th September 2010) - Yashin, Anatoli I.; Arbeev, Konstantin G.; Akushevich, Igor; Arbeeva, Liubov; Kravchenko, Julia; Il'yasova, Dora; Kulminski, Alexander; Akushevich, Lucy; Culminskaya, Irina; Wu, Deqing; Ukraintseva, Svetlana V.
Abstract : It is well known from epidemiology that values of indices describing physiological state in a given age may influence human morbidity and mortality risks. Studies of connection between aging and life span suggest a possibility that dynamic properties of age trajectories of the physiological indices could also be important contributors to morbidity and mortality risks. In this paper we use data on longitudinal changes in body mass index, diastolic blood pressure, pulse pressure, pulse rate, blood glucose, hematocrit, and serum cholesterol in the Framingham Heart Study participants, to investigate this possibility in depth. We found that some of the variables describing individual dynamics of the age-associated changes in physiological indices influence human longevity and exceptional health more substantially than the variables describing physiological state. These newly identified variables are promising targets for prevention aiming to postpone onsets of common elderly diseases and increase longevity.